Cilostazol attenuates ventricular arrhythmia induction and improves defibrillation efficacy in swine - Natnicha Kanlop (2018)
Previous reports demonstrated that cilostazol, a phosphodiesterase 3 inhibitor, affected cellular electrophysiology and reduced episodes of ventricular fibrillation (VF) in patients with Brugada syndrome. However, its effects on VF induction and defibrillation efficacy have never been investigated. We tested the hypothesis that cilostazol increases the VF threshold (VFT) and decreases the upper limit of vulnerability (ULV) and the defibrillation threshold (DFT). A total of 48 pigs were randomly assigned to defibrillation and VF induction studies. The diastolic pacing threshold (DPT), VFT, ULV, DFT, and effective refractory period were determined before and after the infusion of cilostazol at 6 mg/kg, 3 mg/kg, or vehicle. The DPT was significantly increased after administration of 3 and 6 mg/kg cilostazol. The ULV and DFT were significantly decreased after administration of 6 mg/kg cilostazol only. The ULV in the 6 mg/kg group had 12% lower peak voltage and 25% lower total energy, and the DFT had 13% lower peak voltage and 25% lower total energy. The VFT was not altered in any experimental group. This study shows that cilostazol administration significantly increased the DPT, which was associated with significantly reduced DFT and ULV.